What do people value in urban green? Linking characteristics of urban green spaces to users' perceptions of nature benefits, disturbances, and disservices - Julia Palliwoda (Resilience Alliance, 2021)
Now, and in the future, the majority of the world's population is and will be living in cities. Thus, efficient urban green spaces (UGS), such as urban parks providing ecosystem services, are essential for human well-being. Besides their location, the characteristics of UGS, for example, size, availability of facilities (such as sports infrastructure or benches), and green characteristics, can determine the benefits derived or disturbances and disservices perceived by visitors. Knowing which components of UGS contribute to which benefits can help to meet the various demands of urban dwellers. The objective of this research is to present positive and negative aspects (benefits and disturbances/disservices, respectively) of UGS that people perceive and the difference in these perceptions across age groups and UGS. We surveyed more than 1700 users of 18 urban parks and 18 brownfields in Leipzig, Germany. Benefits related to natural elements and landscape aesthetics were most important especially for older age groups. Younger people placed more importance on size, availability, and location as well as sports facilities. The most frequently mentioned disturbance/disservice in urban parks was litter followed by the undesirable activities of other users. Tree cover, sports facilities, seating possibilities, and inhabitant density in the neighborhood influenced the perception of parks providing regulating services (noise mediation and shade provision) and social and cultural interactions. Brownfields were often appreciated as additional UGS close to people's homes and for their wilderness aspects. Implementing specific facilities and varying tree cover can influence perceived benefits from UGS. Adapted management measures can therefore increase multiple benefits and minimize trade-offs between UGS users and uses, for example, the integration of wild areas into UGS including low or near-natural management areas.